Inovasi Pengembangan Konten Website melalui Essential Credibility Checklist di Yayasan Infaq Malaysia - Kholik, Abdul; Sari, Wina Puspita; Soegiarto, Asep; Hijrawadi, Sony Nugratama (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Digital transformation has become a key driving force in global sustainable development, yet many nonprofit organizations still face challenges in optimizing their digital platforms for effective stakeholder communication. This community service activity aimed to enhance the digital public relations competency of Yayasan Infaq Malaysia (YIM) through optimization of the infaqfoundation.org website to support the achievement of Sustainable Development Goals (SDGs) 4 and 8. The methodology employed a systematic four-stage approach including socialization, comprehensive training in website management and content strategy, implementation with one-month mentoring, and development of program sustainability guidelines. The workshop was conducted on July 28-29, 2025, using a User-Centered Design (UCD) framework and website credibility evaluation based on five main dimensions: basic information transparency, leadership governance, financial transparency, program and impact documentation, and technical website quality. Results showed an improvement in website credibility through implementation of responsive design, typography enhancement, navigation optimization, and addition of interactive elements that increased user experience. This activity successfully transformed YIM's digital capacity, strengthened organizational transparency, and created an adaptive and sustainable digital education intervention model to support in accessing educational and career information.ABSTRAKTransformasi digital telah menjadi kekuatan penggerak utama dalam pembangunan berkelanjutan global, namun banyak organisasi nirlaba masih menghadapi kendala dalam mengoptimalkan platform digital untuk komunikasi yang efektif dengan stakeholder. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kompetensi digital public relations Yayasan Infaq Malaysia (YIM) melalui optimalisasi website infaqfoundation.org guna mendukung pencapaian Sustainable Development Goals (SDGs) 4 dan 8. Metodologi yang diterapkan menggunakan pendekatan sistematis empat tahap meliputi sosialisasi, pelatihan komprehensif dalam pengelolaan website dan strategi konten, implementasi dengan pendampingan selama satu bulan, dan pengembangan panduan keberlanjutan program. Workshop dilaksanakan pada 28-29 Juli 2025 dengan menggunakan kerangka User-Centered Design (UCD) dan evaluasi kredibilitas website berdasarkan lima dimensi utama: transparansi informasi dasar, tata kelola kepemimpinan, keterbukaan keuangan, dokumentasi program dan dampak, serta kualitas teknis website. Hasil kegiatan menunjukkan peningkatan kredibilitas website melalui implementasi desain responsif, peningkatan tipografi, optimalisasi navigasi, dan penambahan elemen interaktif yang meningkatkan user experience. Kegiatan ini berhasil mentransformasi kapasitas digital YIM, memperkuat transparansi organisasi, dan menciptakan model intervensi pendidikan digital yang adaptif dan berkelanjutan untuk mendukung pemberdayaan dalam mengakses informasi pendidikan dan karier.